Diary of a wimpy kid; the third wheel - Kinney,Jeff (Penguin, 2009)
The Diary of a Wimpy Kid: The Third Wheel is a continuation of the life of Greg. in this section, Greg has to find a date for the Valentine's Day dance at school. At first Greg is anxious that he cannot get any girl to go with him to the dance. Consulting his friend Rowley also proves to be unhelpful.